RETRACTED: Laparoscopic vs. Open Pancreaticoduodenectomy After Learning Curve: A Systematic Review and Meta-Analysis of Single-Center Studies - Feng, Qingbo; Xin, Zechang; Qiu, Jie; Xu, Mei (Frontiers in Surgery, 2021)
Background Although laparoscopic pancreaticoduodenectomy (LPD) is a safe and feasible treatment compared with open pancreaticoduodenectomy (OPD), surgeons need a relatively long training time to become technically proficient in this complex procedure. And the incidence of complications and mortality of LPD will be significantly higher than that of OPD in the initial stage. This meta-analysis aimed to compare the safety and overall effect of LPD to OPD after learning curve based on eligible large-scale retrospective cohorts and randomized controlled trials (RCTs), especially the difference in the perioperative and short-term oncological outcomes. Methods PubMed, Web of Science, EMBASE, Cochrane Central Register, and ClinicalTrials.gov databases were searched based on a defined search strategy to identify eligible studies before March 2021. Only clinical studies reporting more than 40 cases for LPD were included. Data on operative times, blood loss, and 90 days mortality, reoperation, length of hospital stay (LOS), overall morbidity, Clavien-Dind≥3 complications, postoperative pancreatic fistula (POPF), blood transfusion, delayed gastric emptying (DGE), post-pancreatectomy hemorrhage (PPH), and oncologic outcomes (R0-resection, lymph node dissection, positive lymph node numbers and tumor size) were subjected to meta-analysis. Results Overall, the final analysis included 13 retrospective cohorts and 1 randomized controlled trials comprising 2,702 patients (LPD:1,040, OPD:1,662). It seems LPD has longer operative time (WMD:74.07; 95% CI 39.87--108.26; p< 0.0001). Nevertheless, compared with OPD, LPD was associated with a higher R0 resection rate (odds ratio(OR):1.43; 95% CI 1.10--1.85; p＝0.008) , lower rate of wound infection (OR: 0.35; 95% CI 0.22--0.56; p< 0.0001), less blood loss (WMD: −197.54 ml; 95% CI -251.39 to - 143.70; p< 0.00001) and lower blood transfusion rate (OR: 0.58; 95% CI 0.43--0.78; p＝0.0004) and shorter LOS (WMD: -2.30 day; 95% CI -3.27 to -1.32; p< 0.00001). No significant differences in 90-day mortality, overall morbidity, Clavien-Dindo≥3 complications, reoperation, POPF, DGE, PPH, lymph node dissection, positive lymph node numbers and tumor size between LPD and OPD. Conclusions Comparative studies indicate that after learning curve, LPD is a safe and feasible alternative to OPD. And LPD provides less blood loss, blood transfusion, wound infection and shorter hospital stay when compared with OPD.